Do espírito da coisa: um cálculo de graça - Slemenson, Karin de Paula (2007)
This thesis proposes an understanding of the operations that are involved in a psychoanalytic trajectory by means of the sharpness and the effects produced by the Witz, understood, here, as 'witty and spirituous trace'. In this perspective, the Witz generates a possibility of knowingtodo with the nonsense, without intending to refuse its condition of being impossible to grasp. The trajectory of a psychoanalytic process is proposed here as the one that demands the passage from a dramatic experience, lived in everyday life, to its tragic condition, which is unveiled in the context of the analysis. Such a passage means the aggravation of the lived experience that had brought someone to an analytical experience. Once psychoanalysis is not a sinister practice, the thesis considers a new unfolding of the psychoanalytical experience which would mean finding a trace of grace in the place that, for the one in analysis, was formerly of death. That would be thus a condition for and derived from the analytical trajectory, as well as for the end of a psychoanalysis which would request the one in analysis to coexist with the nonsense and, from this point on, to build his/her voice, therefore inscribing his/her singular participation in human community. Triggering the spirit of The Thing depends on a 'calculus of grace' to be made by the one who positions him/herself as being ready to bet his/her anguish and to afford the aggravations that are part of the psychoanalytic experience